Perlawanan dan Romansa dalam Novel Maut dan Cinta Karya Mochtar Lubis: Kajian Postkolonial - Asia M; Ridwan; Rahmah Indryani (LPPM STKIP PGRI Bandar Lampung, 2024)
This research focuses on analyzing the novel Maut dan Cinta by Mochtar Lubis with a postcolonial approach. This research uses a qualitative description method, which is a research method that explains an event and the condition of the problems contained in the novel. This research uses data processing techniques carried out by reading and interpreting quotation data contained in the novel Maut dan Cinta using a postcolonial approach. Then the data obtained is collected and analyzed using postcolonial theory. The results of the analysis of the novel Maut dan Cinta illustrate the impact of colonialism on society, culture, and individuals as well as how the characters in the novel Maut dan Cinta react to fight colonial hegemony. Mochtar Lubis' Maut dan Cinta depicts how the struggle for independence affects the lives and relationships of the main characters. Conflict, violence, and loyalty to the ideals of nationalism become central themes.